Comparison of culture of synovial fluid, periprosthetic tissue and prosthesis sonicate for the diagnosis of knee prosthesis infection - Trampuž, Andrej (Zdravniški vestnik, 2003)
Background. Synovial fluid and periprosthetic tissue specimens are the standard specimens cultured for the diagnosis of prosthetic joint infection (PJI). We hypothesize that ultrasonication of the explanted prosthesis may improve diagnosis of PJI by dislodging biofilm bacteria from the prosthesis surface and improve the sensitivity and specificity of diagnosis of PJl. Methods. Included were patients undergoing knee prosthesis exchange for septicor biomechanical failure and have not received antimicrobial therapy in the last 2 weeks prior specimen collection. Cultures of synovial jluid and periprosthetic tissue specimens were performed per the usual clinical practice. Additionally, explanted joint components were sonicated for 5 minutes at frequency 40 kHz in sterile Ringer solution; aliquots of 0.5 ml sonicate were plated onto five aerobic and five anaerobic blood agar plates, and incubated at 37degrees C and examined for the next seven days. The numberand identity of each colony morphology was recorded. Results. 35 patients undergoing knee replacement have been studied (24 for aseptic biomechanical failure and 11 for suspected PJI). In patients with PJl, coagulase-negative staphylococci (7 cases), Corynebacterium spp. (2 cases), Staphylococcus aureus (1 case), and viridans group streptococcus (1 case) wererecovered. Culture sensitivity and specificity were for synovial fluid 88%and 100%, for periprosthetic tissue 83% and 81%, and for explant sonicate 91 % and 100% respectively. In sonicate cultures higher numbers of microorganisms than in periprosthetic tissue cultures were consistently detected. (Abstract truncated at 2000 characters).
Keywords: Aparat, onsesnaženje; Biofilmi; Biofilms; Diagnosis; diagnostika; Equipment Contamination; Infection; Infekcija; infekcije; Knee Joint; Knee Prosthesis; Kolenski sklep; Kolenski sklep, proteza; Microbiology; mikrobiološka diagnostika; Prosthesis Failure; Proteza, odpoved; proteze; Sinovialna tekočina; Synovial Fluid; Ultrasonography